2020
DOI: 10.1002/ente.202000223
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Dual‐Ion Batteries via the Reversible Storage of Pyr14+Cations into Coronene Crystal

Abstract: Dual‐ion batteries with pure ionic liquid electrolyte (IL‐DIBs) have received increasing interest due to their sustainability, high operating voltage, and environmental friendliness. However, owing to the insertion/extraction of large‐size ionic liquid cations, the conventional IL‐DIBs with a graphite anode suffer from severe volume expansion and graphite exfoliation on the anode, causing a poor cycling performance. Herein, a novel IL‐DIB is constructed by introducing a bulk organic material (coronene) as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…The less binding energy value of −0.90 eV for one BMP intercalation could also be the reason for the experimentally observed poor Coulombic efficiency (60%) for the early stages of the charging process. 48 A subsequent intercalation of BMP cations leads to an increase in the binding energy value up to 1.71 eV. This as well gets reflected in the increase of the overall Columbic efficiency to 80−90%, observed experimentally.…”
Section: Methodsmentioning
confidence: 74%
See 4 more Smart Citations
“…The less binding energy value of −0.90 eV for one BMP intercalation could also be the reason for the experimentally observed poor Coulombic efficiency (60%) for the early stages of the charging process. 48 A subsequent intercalation of BMP cations leads to an increase in the binding energy value up to 1.71 eV. This as well gets reflected in the increase of the overall Columbic efficiency to 80−90%, observed experimentally.…”
Section: Methodsmentioning
confidence: 74%
“…Owing to the lack of an exact experimental evidence of the BMP-AlCl 4 DGB, we have compared our calculated voltage values with the BMP-TFSI DGB, where both AlCl 4 and TFSI are used as an active intercalant anion species in the DIB study. The experimental voltage window was observed in the range of 1.0−4.6 V for the BMP-TFSI, with a very high voltage discharge plateau achieved at 3.7 V. 48 However, this observation is also reflected in our calculated voltage trends of BMP-AlCl 4 DGB, where the highest discharge voltage value is found to be 3.79 V. Furthermore, our calculated relative energy and the literature study have suggested that the formation of stage-4 is feasible in the case of both BMP and AlCl 4 intercalation into the graphite at the initial state of charging. The average voltage of the stage-2 BMP-stage-4 AlCl 4 is calculated to be 3.29 V, which lies in the range of the experimental voltage window.…”
Section: Methodsmentioning
confidence: 88%
See 3 more Smart Citations